Molecular Networking: A Useful Tool for the Identification of New Psychoactive Substances in Seizures by LC–HRMS - Vincenti, Flaminia; Montesano, Camilla; Di Ottavio, Francesca; Gregori, Adolfo; Compagnone, Dario; Sergi, Manuel; Dorrestein, Pieter (Frontiers in Chemistry, 2020)
New Psychoactive Substances (NPS) are a global concern sincebecause they are spreading at an unprecedented rate.; Despite even if their commerce is still limited when compared to traditional illicit drugs, the identification of NPS in seizures may represent a challenge because of the variety of possible structures. In this study we report the successful application of molecular networking (MN) to identify unexpected fentanyl analoguess in two analysed seizures. The samples were extracted with 1 mL of methanol and analysedanalysed with an untargeted data-dependent acquisition approach by LC–HRMS. The obtained data were analysed examined using the MN workflow within the Global Natural Product Search (GNPS). A job was submitted to GNPS by including both Data of seizures and were analysed along with raw files of standard mixtures containing synthetic cannabinoids and fentanyls, standard mixtures raw files; standard spectra obtained from standards were used to establish a representative networks for both molecular classes. All synthetic cannabinoids in the mixture were linked together resulting in ain a molecular network despite theirexhibiting different fragmentation spectra. ;Looking at on the other hand, only fentanyls, all the molecules with the typical 188.143 and 105.070 fragments were combined in a representative network. By exploiting the standard networks obtained with standard solutions two unexpected fentanyls were found in the analyzed seizures and , they were putatively identified annotated as para-fluorofuranylfentanyl and (iso)butyrylfentanyl. The identity of these two fentanyl analogues was confirmed by NMR analysis. Other m/z ratios in the seizures were compatible with fentanyl derivatives; however, they appeared to be minor constituents, probably impurities or synthetic byproducts.; The latter might betheir detection may be of interest for investigations of for the identification of common fingerprints among differentbetween seizures.